Cloherty and Stark's manual of neonatal care - Eichenwald, Eric C.; Hansen, Anne R.; Martin, Camilia; Stark, Ann R. (Lippincott manual., 2017)
"Concise and easy to read, this popular manual has provided a practical approach to the diagnosis and medical management of problems in the newborn through seven outstanding editions. The Eighth Edition of Cloherty and Stark's Manual of Neonatal Care maintains that tradition of excellence, offering NICU physicians, neonatal-perinatal fellows, residents, and neonatal nurse practitioners quick access to key clinical information, fully updated to reflect recent advances in the field. Written in an easy-access outline format, this extensively revised edition covers current, practical approaches to the evaluation and management of routine and complex conditions encountered in the fetus and the newborn"--Publisher's description